Martial Arts and Well-Being : Connecting Communities and Promoting Health - Fuller , Carol; Lloyd, Viki (Taylor & Francis, 2020)
Arts; being; Carol; communities; Connecting; Fuller; Health; Llyod; Martial; promoting; Viki; well
English
Keywords: Psychology; Social, group or collective psychology; Sports psychology; Combat sports & self-defence; Arts; being; Carol; communities; Connecting; Fuller; Health; Llyod; Martial; promoting; Viki; well